Biochemical characteristics of patients with imported malaria - Bi, Dewu; Lin, Jianyan; Luo, Xiaolu; Lin, Lü; Tang, Xike; Luo, Xiaocheng; Lu, Yuexi; Huang, Xiaodong (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives The present study aimed to investigate the clinical and biochemical profiles of patients with imported malaria infection. Methods Analysis of clinical and biochemical profiles in a cohort study of 170 patients who had been conformed imported malaria infection. Malaria parasite clearance was defined as the primary outcome. Multivariable logistic regression model was adopted to evaluate the odds ratios with 95% confidence intervals of cerebral malaria. The Cox model was used to estimate hazard ratios with 95% confidence intervals of parasite clearance. Results Adenosine deaminase and parasitemia are independent risk factor for severe malaria in patients with imported malaria (OR=1.0088; [95%CI: 1.0010-1.0167]; p=0.0272) and (OR=2.0700; [95%CI: 1.2584-3.4050]; p=0.0042). A 0.5-SD increased of variation for urea (HR 0.6714, [95% CI 0.4911-0.9180]), 0.5-SD increased of variation for creatinine (HR 0.4566, [95% CI 0.2762-0.7548]), 0.25-SD increased of variation for albumin (HR 0.4947, [95% CI 0.3197-0.7653]), 0.25-SD increased of variation for hydroxybutyrate dehydrogenase (HR 0.6129, [95% CI 0.3995-0.9402]), and 1.0-SD increased of variation for ferritin (HR 0.5887, [95% CI 0.3799-0.9125]) was associated with a higher risk of duration for parasites clearance than low level change. Conclusions Aspartate aminotransferase, urea, creatinine, albumin, hydroxybutyrate dehydrogenase, and ferritin are useful biochemical indicators in routine clinical practice to evaluate prognosis for imported malaria.